2014
DOI: 10.1002/hed.23781
|View full text |Cite
|
Sign up to set email alerts
|

In‐office cup biopsy and laryngeal cytology versus operating room biopsy for the diagnosis of pharyngolaryngeal tumors: Efficacy and cost‐effectiveness

Abstract: In-office biopsy is a more affordable technique that enables histologic diagnosis of pharyngolaryngeal lesions in a large percentage of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 14 publications
3
42
0
Order By: Relevance
“…In retrospect, the fourth case may not have had a compromised airway during biopsy, but he did have a compromised airway, which required a tracheotomy, when he was admitted to the emergency department. In some studies, anticoagulant use was considered a relative contraindication; patients were advised to stop anticoagulation use, defer the procedure, or they were excluded from further analysis [6, 7, 14, 15]. In the current study, anticoagulant use was not considered a contraindication and it was reported in 29.9% of the patients who underwent FEB. One of four patients (25%) with a complication in this cohort used anticoagulants but did not develop bleeding.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…In retrospect, the fourth case may not have had a compromised airway during biopsy, but he did have a compromised airway, which required a tracheotomy, when he was admitted to the emergency department. In some studies, anticoagulant use was considered a relative contraindication; patients were advised to stop anticoagulation use, defer the procedure, or they were excluded from further analysis [6, 7, 14, 15]. In the current study, anticoagulant use was not considered a contraindication and it was reported in 29.9% of the patients who underwent FEB. One of four patients (25%) with a complication in this cohort used anticoagulants but did not develop bleeding.…”
Section: Discussionmentioning
confidence: 85%
“…The histology result of laryngeal FEB was positive for malignancy (i.e., malignant result), negative for malignancy (i.e., nonmalignant result), or non-diagnostic. A non-diagnostic result could occur when it was impossible to obtain a biopsy specimen or when no histological diagnosis could be determined in case of superficially obtained tissue [15]. In the case of an established malignancy, the treatment could be determined by the multidisciplinary tumor board immediately.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the routine use and interpretation of OBB are controversial . Cohen et al recommended the verification with ORB when the pathology of OBB was reported as benign or premalignancy.…”
Section: Introductionmentioning
confidence: 99%